Mobile Augmented Reality for Human Scale Interaction with Geospatial Models The Benefit for Industrial Applications - Schall, Gerhard; SpringerLink (Online service) (Wiesbaden : Springer Fachmedien Wiesbaden : Imprint: Springer Gabler, 2013)
Gerhard Schall overviews research activities related to mobile augmented reality in indoor as well as outdoor environments. These activities have emerged over several years, especially around the topics of positioning, sensor fusion, spatial modelling as well as in the fields of ubiquitous computing. The author gives insights into the evolution of mobile augmented reality prototypes for industrial applications, such as the X-ray visualisation of 3D models of the underground infrastructure which is registered correctly in the users view.
Mobile Augmented Reality -- Geospatial Modelling of Underground Infrastructure -- Interactive Urban Models -- Indoor Tracking -- Outdoor Tracking -- Civil Engineering.
Keywords: Economics; Management information systems; Economics/Management Science; Business Information Systems